«Time preference and investment expenditure»: comment on Hülsmann - Méra, Xavier Méra (REVISTA PROCESOS DE MERCADO, 2011)
Hülsmann (2008) argues that the neglect of time preference changes on the demand side of the time market renders Rothbard’s (1993) analysis incomplete in that it unduly portrays a rise in the volume of investment as a necessary counterpart to a fall in the pure interest rate. Focusing on the determinants of the demand for present goods, this paper shows that though Hülsmann’s strictures are essentially valid, Rothbard has actually explained why the direct impact of time preference changes should display themselves mostly on the supply side. However, the implications have been neglected both by Hülsmann and Rothbard. We explore these implications, demonstrating that the present demand schedule and the volume of investment should be considered as mostly independent from present time preferences and determined instead by past production decisions. We show how this approach allows for a more «dynamic» understanding of the time market and growth processes. Key words: Time Preference, Investment Expenditure, Time Market, Structure of Production, Interest Rate, Growth Types, Austrian Macroeconomics. JEL Classification: B53, E22, E23, E43, O11, O16, O40. Resumen: Hülsmann (2008) argumenta que pasar por alto los cambios en la preferencia temporal del lado de la demanda en el mercado de tiempo hace incompleto el análisis de Rothbard (1993) al representar indebidamente un incremento en el volumen de inversión como contrapartida necesaria a una caída en la tasa de interés pura. Centrándose en los determinantes de la demanda para bienes presentes, este paper muestra que, siendo las críticas de Hülsmann esencialmente válidas, Rothbard realmente explicó por qué el impacto directo de los cambios en la preferencia temporal debería reflejarse fundamentalmente en el lado de la oferta. Sin embargo, las implicaciones derivadas de ello fueron ignoradas por Hülsmann y Rothbard. Las exploraremos, demostrando que la curva de demanda presente y el volumen de inversión deberían considerarse esencialmente independientes de las preferencias temporales presentes, estando determinadas realmente por decisiones pro-ductivas pasadas. Esta aproximación permite una comprensión más «diná-mica» del mercado de tiempo y los procesos de crecimiento. Palabras clave: Preferencia temporal, gasto de inversión, mercado del tiempo, estructura de la producción, tipo de interés, tipos de crecimiento, macroeconomía austriaca. Clasificación JEL: B53, E22, E23, E43, O11, O16, O40.